(untitled) (World Bulletin of Management and Law, 2023)
The article is devoted to analysis of corporate criminal liability. The article also analyzes the prospect of the introduction of such responsibility in criminal law. Like any other innovation it has its advantages and disadvantages, which is also discussed in this article. In addition, the article author analyzed the positive and negative features of the introduction of this institution. The author used different research methods such as: method of system analysis, the historical-legal method, and comparative legal method.